The Role of Metacognitive Skills in Developing The 21st Century Skills - Ade Mardiana Damayanti; Nur Syamsiyah; Endang Astuti; Uci Dania; Pintaka Kusumaningtyas (Faculty of Teacher Training and Education, Mulawarman University, 2021)
Metacognition is one of the most important dimensions of education in building knowledge, skills and character of students. The metacognitive skills are indispensable in developing the 21st century skills that must be mastered by students. This paper provides a review of literature that emphasizes on the 21st century skills that can be developed through the metacognition in learning. The finding reported the 21st century skills that can be developed in learning using the metacognitive skills included the ability in problem solving, critical thinking, reflective thinking and accessing information. As such, it can be concluded that the metacognitive skills of students can be one of the key factors in students’ successful in mastering the 21st century skills.